The Relationship Between Increased Neutrophils and Length of Hospitalization in Pediatric Pneumonia Patients - Ade Amelyani Saputri; Abdi Dwiyanto Putra Samosir; Maya Susanti; A. Husni Esa Darussalam; Nur Aisya (Journal La Medihealtico, 2026)
Pneumonia remains one of the major respiratory infections affecting children and is often associated with increased morbidity, prolonged hospitalization, and higher healthcare burden. Neutrophils play an important role in the inflammatory response to infection and may serve as a useful laboratory indicator for evaluating disease severity and clinical outcomes in pediatric pneumonia. This study aimed to determine the relationship between increased neutrophil levels and length of hospitalization among pediatric pneumonia patients at Ibnu Sina Hospital Makassar during January to December 2025. This research used an observational analytic design with a cross sectional approach based on secondary data from medical records. The study population consisted of pediatric patients aged 0 to 18 years diagnosed with pneumonia, with complete blood count data available. Data were analyzed using univariate and bivariate analysis, with the Chi Square test applied to determine statistical significance. The results showed that most pediatric pneumonia patients were aged 1 to 10 years, were slightly more likely to be male, and were predominantly treated as inpatients. Most patients had a length of hospitalization of more than 4 days. Neutrophil examination showed that 50 patients had increased neutrophil levels, 38 had normal levels, and 9 had decreased levels. The analysis demonstrated a significant relationship between neutrophil levels and the incidence of pneumonia with a p value of 0.046. Furthermore, increased neutrophil levels were significantly associated with length of hospitalization, with a p value of 0.001. These findings indicate that increased neutrophil levels may reflect the severity of inflammatory response in pediatric pneumonia and may be useful as a clinical indicator for predicting longer hospitalization.